2023
DOI: 10.26508/lsa.202302133
|View full text |Cite
|
Sign up to set email alerts
|

The CHARGE syndrome-associated protein FAM172A controls AGO2 nuclear import

Abstract: CHARGE syndrome is a neural crest-related disorder mainly caused by mutation of the chromatin remodeler-coding geneCHD7. Alternative causes include mutation of other chromatin and/or splicing factors. One of these additional players is the poorly characterized FAM172A, which we previously found in a complex with CHD7 and the small RNA-binding protein AGO2 at the chromatin–spliceosome interface. Focusing on the FAM172A–AGO2 interplay, we now report that FAM172A is a direct binding partner of AGO2 and, as such, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…Recent studies revealed competitive binding of TNRC6 to various proteins involved in RNA destabilization, such as TRIM71 and UPF1 [27], therefore, RNAi efficiency also depends on the TNRC6 pool available for AGO binding. Nuclear import of AGO:miRNA complexes was linked with Importin 8 in HeLa cells and more recently to FAM172A in mouse embryonic fibroblasts [17,[28][29]. Nevertheless, the underlying molecular mechanisms of AGOs activity, translocation and subsequent RNAi-mediated gene regulation in the nucleus of cancer cells remains to be fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed competitive binding of TNRC6 to various proteins involved in RNA destabilization, such as TRIM71 and UPF1 [27], therefore, RNAi efficiency also depends on the TNRC6 pool available for AGO binding. Nuclear import of AGO:miRNA complexes was linked with Importin 8 in HeLa cells and more recently to FAM172A in mouse embryonic fibroblasts [17,[28][29]. Nevertheless, the underlying molecular mechanisms of AGOs activity, translocation and subsequent RNAi-mediated gene regulation in the nucleus of cancer cells remains to be fully explored.…”
Section: Introductionmentioning
confidence: 99%